Pengaturan Karantina Tumbuhan dalam Pengawasan Buah Impor di Indonesia - Ni Putu Wirastha Wisnuswari; I Nyoman Putu Budiartha; Desak Gede Dwi Arini (Jurnal Preferensi Hukum, 2021)
The practice of applying chemical substances to fruits to keep them fresh and look fresh is still being discovered. This form of fraud can occur and can pass into the fruit market in Indonesia in the absence of an agency that specifically pays attention to and carries out quarantine. The purposes of this study are to reveal the plant quarantine arrangements in the provisions of the legislation on the supervision and model for imported fruit that will be marketed and consumed by the public. The type of research used in this research is normative legal research. Sources of legal materials used are primary, secondary and tertiary sources of law. The technique of collecting legal materials used in this research is the technique of document study and literature study. After the data is collected, then it is analyzed descriptively. The results of the study show that the regulation of plant quarantine is in the Law of the Republic of Indonesia Number 21 of 2019 concerning Animal, Fish and Plant Quarantine and is also regulated in Government Regulation Number 14 of 2002 concerning Plant Quarantine. The control model for imported fruit to be marketed and consumed by the public is carried out according to the procedure, namely that each carrier medium (plants and their parts and/or other objects) is subject to plant quarantine, physical/visual inspection is carried out and continued with health checks according to the OPTK target.